Digital mantras the languages of abstract and virtual worlds - Holtzman, Steven R. (MIT Press, 1994)
Holtzman synthesizes ideas from music, computing, art, and philosophy with biographical and historical anecdotes and a thread of mysticism to arrive at a new philosophy of creativity for the digital age.
Keywords: Computers.; Virtual reality.; elektronické knihy; electronic books